The economics of recreation, leisure and tourism - Tribe, John (Butterworth-Heinemann, 2011)
This textbook describes the relevance of economics to the tourism and leisure industries, helping you to pass an economics module as part of a tourism, recreation or sport management degree. It applies economic theory to a range of tourism industry issues at the consumer, business, national and international level by using topical examples to give the theory real-world context. The author explains the impact of the global economic crisis and the importance of understanding what has happened over the course of previous economic business cycles to prepare for what may happen in the future. Contrasting evidence is put forward to provide a sense of the dynamics of world economies.